Answer:
Step-by-step explanation:
1. This point is not clear.
2.
[tex]4-\frac{f}{5}=f+\frac{1}{3}\\\\4-\frac{1}{3}=f+\frac{f}{5}\\\\\frac{11}{3}=\frac{6f}{5}\\\\f=\frac{55}{18}[/tex]
3.
[tex]-\frac{3}{2g}+1=\frac{3}{g}+6\\\\-\frac{3}{2g}-\frac{3}{g}=6-1\\\\-\frac{9}{2g}=5\\\\g=-\frac{9}{10}[/tex]
4.
[tex]\frac{-1}{-h}-4=\frac{2}{h}-4\\\\\frac{-1}{-h}=\frac{2}{h}\ \ \[/tex]
it does not have solution or is not clear
5.
[tex]5k-\frac{2}{-4}=2-\frac{5k}{4}\\\\5k+\frac{5k}{4}=2+\frac{2}{-4}=2-\frac{2}{4}\\\\\frac{25}{4}k=\frac{3}{2}\\\\k=\frac{6}{25}[/tex]
6.
[tex]-6m-\frac{3}{4}=2m+\frac{5}{-2}\\\\-6m-2m=-\frac{5}{2}+\frac{3}{4}\\\\-8m=-\frac{14}{8}\\\\m=\frac{14}{64}=\frac{7}{32}[/tex]